Agentes asociados al "colapso del melon" en distintas zonas españolas - Garcia-Jimenez, J.=700 1 Martinez-Ferrer, G.; Armengol, J.; Velazqquez, M.T.; Orts, M.; Juarez, M.; Ortega, A.; Jorda, M.C.; Alfaro, A.
(En, Es)
ilus., 24 ref.
Keywords: CUCUMIS MELO; COLAPSO; HONGOS; ACREMONIUM; MONOSPORASCUS; MACROPHOMINA PHASEOLINA; RHIZOCTONIA SOLANI; ESPAÑA